2021
DOI: 10.1002/pon.5829
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric symptoms mediate the effect of resilience on health‐related quality of life in patients with breast cancer: Longitudinal examination

Abstract: Objective Patients with breast cancer receiving neoadjuvant chemotherapy are at increased risk of poor health‐related quality of life (HRQOL). This study examined clinical caseness on depression and anxiety mediate the relationship between resilience and HRQOL in patients with breast cancer. Methods A total of 193 patients with breast cancer undergoing neoadjuvant chemotherapy completed questionnaires including the Connor–Davidson Resilience Scale, Hospital Anxiety and Depression Scale (HADS), and Functional A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Patients with BC with late chronotype have an increased risk of CINV during NAC. In another study, Lee et al 31 indicated that depression during NAC was a mediator in the relationship between resilience and health-related QOL in patients with BC, and QOL after NAC can be improved by screening and intervening for depression during NAC in patients with BC. Meanwhile, Takada et al 29 reported that high QOL before chemotherapy was an independent factor in overall survival ( table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients with BC with late chronotype have an increased risk of CINV during NAC. In another study, Lee et al 31 indicated that depression during NAC was a mediator in the relationship between resilience and health-related QOL in patients with BC, and QOL after NAC can be improved by screening and intervening for depression during NAC in patients with BC. Meanwhile, Takada et al 29 reported that high QOL before chemotherapy was an independent factor in overall survival ( table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies were designed as prospective cohort studies,20–25 three were RCTs,26–28 one was a retrospective cohort study29 and one was a cross-sectional study 30. Two studies were each from Brazil25 27 and Korea,21 31 and one each from China,20 Japan,29 India,22 UK,26 Germany,23 Indonesia,30 Iran24 and the USA 28. One study compared QOL in BC patients with NAC and adjuvant therapy,25 and three studies compared QOL in patients with different regimens of NAC 22 24 26.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A significant number of cancer patients have psychological problems (depression, anxiety, cognitive impairment, etc.) following chemotherapy treatment that further reduces the quality of lifestyle ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%